Implementasi E-Modul Flippingbook pada Materi Teks Eksposisi untuk Meningkatkan Higher Order Thinking Skills Siswa Kelas X SMA - Ramadhani, Irma; Ali, Ali; Kartika, Rika; Soraya, Ratna (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2024)
This study employed the Research and Development (R&D) model to create and evaluate flipping book-assisted E-Module learning products for exposition text material aimed at enhancing Higher Order Thinking Skills (HOTS) in class X at SMA N 19 Medan. The research sought to determine the feasibility and effectiveness of the developed E-Module. The study's population included 400 class X students, with a sample of 39 students from class X-7 selected using purposive sampling. The research followed the ADDIE model, comprising analysis, design, development, implementation, and evaluation stages. Data were collected and analyzed quantitatively, then converted into qualitative insights. Validation by material expert I scored 80% ("quite feasible"), material expert II scored 75.71% ("quite adequate"), media expert I scored 88% ("very feasible"), and media expert II scored 73.33% ("quite decent"). The Indonesian language teacher's response was 89.33% ("very appropriate"), and student responses averaged 85.12% ("very effective"). These results indicate that the flipping book-assisted E-Module for exposition text material is feasible and effective for enhancing HOTS.